ЗВ'ЯЗАНІ ЕЛЕКТРИЧНІ ТА МЕХАНІЧНІ ПРОЦЕСИ В ПОЛІЕТИЛЕНОВІЙ ІЗОЛЯЦІЇ ЗА НАЯВНОСТІ ВОДНИХ ТРИЇНГІВ З ГІЛКАМИ СКЛАДНОЇ СТРУКТУРИ - Кучерява , І.М. (Інститут електродинаміки НАН України, Київ, 2016)
The distributions of electric field, electric force and mechanical stress in the polyethylene insulation of power cable that contains separate branch of a water tree are studied by computer modeling. Two models of water tree branch which include a string of water-filled spherical microcavities connected by cylindrical channels with equal radius and with radius decreasing along the length of the branch are examined. It is shown that the action of electric force and electromechanical stresses at the ends of thinner tree channels can cause their destruction and then growth of water trees in polyethylene insulation. References 15, figures 5, table 1.